Recent Perspectives on the Mechanism of Recurrence After Ablation of Hepatocellular Carcinoma: A Mini-Review - Yang, Jianquan; Guo, Wen; Lu, Man (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is one of the most common malignant tumors. Hepatectomy, liver transplantation, and ablation are the three radical treatments for early-stage hepatocellular carcinoma (ESHCC), but not all patients are fit for or can tolerate surgery; moreover, liver donors are limited. Therefore, ablation plays an important role in the treatment of ESHCC. However, some studies have shown that ablation has a higher local recurrence (LR) rate than hepatectomy and liver transplantation. The specific mechanism is unknown. The latest perspectives on the mechanism of recurrence after ablation of HCC were described and summarized. In this review, we discussed the possible mechanisms of recurrence after ablation of HCC, including epithelial–mesenchymal transition (EMT), activating autophagy, changes in non-coding RNA, and changes in the tumor microenvironment. A systematic and comprehensive understanding of the mechanism will contribute to the research and development of related treatment, combined with ablation to improve the therapeutic effect in patients with ESHCC.